Luminescent Solar Concentrator (LSC) Berbasis Coumarin Terintegrasi dengan Fotovoltaik sebagai Fasad Bangunan Penghasil Energi Listrik - Kerta Adi Wasana; Akbar Sujiwa; Nur Aini Fauziyah (Jurnal Fisika Unand, 2026)
The integration of renewable energy systems in buildings offers a promising approach to enhance the sustainable utilization of clean energy. This study presents the development of a renewable energy prototype based on a Luminescent Solar Concentrator (LSC) integrated with photovoltaic modules for building façade applications. The LSC was fabricated using epoxy resin mixed with coumarin, producing samples with dimensions of 100 cm² and 400 cm². Photovoltaic modules were installed along the edges of the LSC to capture guided light and convert it into electrical energy. The prototype was evaluated using a measurement system that continuously records voltage, current, and power output. Experimental testing was conducted from 07:00 to 16:00 (WIB) under direct sunlight to analyze the system response to variations in solar irradiance. The results indicate that the system produces relatively stable voltage output, while the current and power vary depending on the intensity of solar radiation. The maximum voltage, current, and power obtained were 36.1 V, 1.14 mA, and 40.07 mW, respectively. These findings demonstrate the potential of the proposed LSC–photovoltaic prototype as a renewable energy harvesting system for building applications, particularly within the concept of Building Integrated Photovoltaics (BIPV).